Self-Perceived Vocal Symptoms and Discomfort in Amateur Church Singers - da Silva, Danielle Melo; de Lacerda, Mel Mutiz; Depolli, Gabriel Trevizani [UNESP]; Azevedo, Elma Heitmann Mares; Moreti, Felipe [UNESP]; Guimarães, Michelle Ferreira (Elsevier, 2024)
Purpose: To analyze self-perceived vocal symptoms and discomfort in amateur church singers and compare them between genders and church types. Methods: It was a quantitative cross-sectional study involving 99 amateur church singers aged between 18 and 59 years. Data collection was carried out through the completion of a sociodemographic questionnaire, the Voice Symptom Scale (VoiSS), and the Vocal Tract Discomfort Scale (VTDS). The Mann-Whitney test was used for comparisons, and Spearman's correlation test was used for analyzing correlations between scale scores. The adopted significance level was 5% (P < 0.05). Results: There was a prevalence of females (71.7%), amateur singers from Protestant churches (73.7%), with a mean age of 27.5 years. The average VoiSS total score was 22.6 points, the “limitation” domain was 12.3, the “emotional” domain was 2.55, and the “physical” domain was 7.7. The most self-perceived sensations in the VTDS were “dryness,” sore throat, and “itchiness” with mild to moderate intensity. There was a statistically significant difference between genders (P < 0.05) and a positive correlation from weak (r = 0.212) to strong magnitude (r = 0.660) between vocal symptoms and vocal tract discomfort. There was no statistically significant difference between types of churches. Conclusion: Amateur singers self-report high levels of vocal symptoms, which impact limitation, emotional, and physical domains. Furthermore, they experience vocal tract discomfort sensations, with dryness being the most frequently reported, followed by sore throat and itching. No significant differences were found between the scale scores and church types. However, females reported a greater frequency and intensity of vocal tract discomfort sensations. The greater the self-reported vocal symptoms in this population, the higher their self-reported frequency and intensity of vocal tract discomfort sensations. These findings underscore the importance of addressing vocal health issues in amateur singers to enhance their overall well-being.
Keywords: Music; Signs and symptoms; Singing; Voice; Voice quality